Originally Posted by

**cottontails** I now no longer have any difficulties with (i) and (ii) however, with (iii), I cannot get the correct answer.

My working (using t instead of k, since there is a k vector in the equation):

-> t(3i + γj + 3γk) = 12i - 5k

--> 3t=12, γt=0, 3γt=-5

Whenever I solve the equations simultaneously so, t=4 and substituting that into 3γt=-5, I get γ=-5/12.

Although, am I doing something wrong there since shouldn't that also equal the same (-5/12) with substituting t=4 in γt=0?